Abyssal water mass exchange between the Japan and Yamato Basins in the Japan Sea. Issue 10 (2nd October 2013) - Senjyu, Tomoharu; Aramaki, Takafumi; Tanaka, Shinichi S.; Zhang, Jin; Isoda, Yutaka; Kumamoto, Yuichiro; Hibino, Sho; Nakano, Toshiya
Abstract : [1] Bottom water exchange between the Japan and Yamato Basins in the abyssal Japan Sea is investigated based on data from two research cruises in June 2010 and June 2011. Distributions of water properties and velocity profiles from CTD/LADCP observations revealed a two‐layer water mass exchange in a rotating system. The cold Japan Basin Bottom Water (JBBW) with high dissolved oxygen (DO) concentrations flowed into the Yamato Basin along the northern boundary of the channel connecting the basins, while the warmer, lower‐DO Yamato Basin Bottom Water (YBBW) extended over the JBBW along the southern periphery of the channel. A benthic front between the JBBW and YBBW was observed in both cruises, though the front shifted to the northeast in 2011 compared with its 2010 location. Further, the bottom flows in the channel were not unidirectional in 2011, though consistent southwestward flows were observed in 2010. The JBBW transport into the Yamato Basin was also larger in 2010 than in 2011. Analysis of historical hydrographic data showed that the benthic front exists mostly in the narrowest region of the channel, though it fluctuates temporarily to the northeast or southwest. The fluctuation of the benthic front appears to be associated with the JBBW transport because the observations in June 2010 and June 2011 were carried out during periods of southwestward extension of cold water and northeast protrusion of warm water, respectively. A relationship between benthic front displacements and mesoscale warm eddy migrations is suggested. Key Points: Bottom water exchange between abyssal basins in the Japan Sea is investigated Benthic front and two‐layer water mass exchange in rotating system were revealed Temporal fluctuation of benthic front is related to the warm eddy migrations